PERAN FOUNDER DALAM PENGEMBANGAN KOMUNITAS LARI - Rika Rachmawaty; Renny Nurhasana; Windya Dirgantari; Riesmah Oktapriana; Nofrida Nofrida (LPSDI Bina Patria, 2023)
The popularity of running together among urban societies in line with the growth of the running community. Many runners join the community to get a more enjoyable running atmosphere. Community formation is inseparable from the role of the founders who act as actors who set community goals. Based on this, the focus of this research is the role of the founder in developing the running community. The research was conducted qualitatively by collecting data through in-depth interviews using descriptive analysis methods. The main informants are the founders of the Pemprov DKI Jakarta Runners and Skolari who are in Jakarta. The results of the analysis show that the founder as the leader of the community is involved in every aspect of developing the running community.